2022
DOI: 10.1021/acsmaterialsau.2c00028
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Synthesis of Thin Films for the Discovery of Energy Materials: A Perspective

Abstract: Thin films are an integral part of many electronic and optoelectronic devices. They also provide an excellent platform for material characterization. Therefore, strategies for the fabrication of thin films are constantly developed and have significantly benefited from the advent of high-throughput synthesis (HTS) platforms. This perspective summarizes recent advances in HTS of thin films from experimentalists’ point of view. The work analyzes general strategies of HTS and then discusses their use in developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“… For practical applications of thin films, more straightforward and high-throughput techniques are needed for their mechanical characterization. This is of fundamental importance in order to provide a deep understanding of the mechanical properties of libraries of thin film materials, whose preparation has been recently accelerated by automated synthesis platforms, 80 before their actual implementation in the device; Most of the studies reported up to now were mainly focused on quasi-static properties, while dynamic behavior, fatigue, creep, or viscoelastic relaxation (that can be severe phenomena in the case of polymers) have been scarcely investigated. On the contrary, their investigation is important to enable full functionalities of ultrathin polymeric film devices, especially for high-rate, high-frequency, or long-life applications; It will be exciting to understand the structure-mechanical properties relationship of thin polymeric films.…”
Section: Current Directions and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“… For practical applications of thin films, more straightforward and high-throughput techniques are needed for their mechanical characterization. This is of fundamental importance in order to provide a deep understanding of the mechanical properties of libraries of thin film materials, whose preparation has been recently accelerated by automated synthesis platforms, 80 before their actual implementation in the device; Most of the studies reported up to now were mainly focused on quasi-static properties, while dynamic behavior, fatigue, creep, or viscoelastic relaxation (that can be severe phenomena in the case of polymers) have been scarcely investigated. On the contrary, their investigation is important to enable full functionalities of ultrathin polymeric film devices, especially for high-rate, high-frequency, or long-life applications; It will be exciting to understand the structure-mechanical properties relationship of thin polymeric films.…”
Section: Current Directions and Future Perspectivesmentioning
confidence: 99%
“…For practical applications of thin films, more straightforward and high-throughput techniques are needed for their mechanical characterization. This is of fundamental importance in order to provide a deep understanding of the mechanical properties of libraries of thin film materials, whose preparation has been recently accelerated by automated synthesis platforms, 80 before their actual implementation in the device;…”
Section: Current Directions and Future Perspectivesmentioning
confidence: 99%
“…The progress of many important technologies such as solar cells, light‐emitting diodes, batteries, superconductors, and thermoelectrics rely on how fast materials are discovered or developed. Because the best materials are often a blend of multiple components, high‐throughput experimentations (HTEs), [ 1–33 ] both for making and studying mixtures/alloys, have recently gained major attention. [ 2 ] However, state‐of‐art HTEs are unfortunately able to make only a fraction of possible compositions and then employ machine learning algorithms to extrapolate to unmade compositional space.…”
Section: Introductionmentioning
confidence: 99%
“…Because the best materials are often a blend of multiple components, high‐throughput experimentations (HTEs), [ 1–33 ] both for making and studying mixtures/alloys, have recently gained major attention. [ 2 ] However, state‐of‐art HTEs are unfortunately able to make only a fraction of possible compositions and then employ machine learning algorithms to extrapolate to unmade compositional space. [ 25,33 ] Being able to make all possible alloys simultaneously, in one batch, would provide access to unprecedentedly large material libraries, but this remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation